Autotaxin and vascular endothelial growth factor receptor‐2 and ‐3 are related to vascular development during the progression of chronic viral hepatitis C. Issue 12 (19th November 2018) - Yokomori, Hiroaki; Ando, Wataru; Kaneko, Fumihiko; Suzuki, Hidekazu; Igarashi, Koji; Oda, Masaya
Abstract : Vascular endothelial growth factor (VEGF) and autotaxin (ATX) play important roles in embryonic vasculogenesis and cancer progression. This study examines whether these two angiogenic factors cooperate in the mechanism that regulates vascular development during the progression of chronic viral hepatitis C (CVH‐C) (Inuyama classification, F1–F4). First, surgical wedge biopsy specimens and needle biopsy specimens were obtained. Immunohistochemical staining for ATX and vascular endothelial growth factor receptor was assessed in serial sections. Immunoelectron microscopy was conducted with a perfusion‐fixation method. In normal control liver tissue specimens, ATX was expressed at low levels within the branches of the hepatic artery and hepatic sinusoids. In F1 CVH‐C liver tissue specimens, ATX was expressed within the branches of the hepatic artery. Additionally, VEGFR‐2 was expressed within the branches of the hepatic artery and capillaries. In F3–F4 CVH‐C liver tissue specimens, positive staining for ATX and VEGFR‐2 or VEGFR‐3 was detected in the branches of the hepatic artery or microlymphatic vessels. ATX‐1 reaction products were specifically expressed on the plasma membrane of some microvascular endothelial cells (ECs) in the proliferative capillary artery. VEGFR‐2 was expressed on caveolae in ECs and vascular smooth muscle cells. VEGFR‐3 immunogold particles were also observed in lymphatic ECs. These results suggest functional interactions among ATX, VEGFR‐2, and VEGFR‐3 in the modulation of hemovascular and lymphovascular cell activation during vascular development.